A Template-Based Anthropometric Measurement Approach for 3D Scanned Bodies - Ferreira, Wesley Ferreira de; Balreira, Dennis Giovani; Marcondes Filho, Danilo; Walter, Marcelo (Anais da Conference on Graphics, Patterns and Images (SIBGRAPI); 2023: Anais da XXXVI Conference on Graphics, Patterns and Images, 2023)
Accurate and precise body measurements are es-sential for various applications, including body composition analysis, health assessment, and clothing design. In comparison to traditional manual methods, 3D scanning has emerged as a faster and more reliable alternative. Our work introduces an automated approach for measuring 3D scanned bodies. Given any 3D mesh representing a human body, we convert it to a template and apply curve-level slicing for the measurements. Our validation incorporates statistical measures proposed for compatibility with the ISO and other methods. Our results improve the previous state-of-the-art in Mean Standard Deviation (MAD) by 5.5% and the Standard Error of Measurements (SEM) by 10.7%.